2020
DOI: 10.1186/s40981-020-00367-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted intrathecal injection of nusinersen in a patient with severe vertebral deformity: a case report

Abstract: Background: Spinal muscular atrophy (SMA) is a mostly autosomal recessive genetic disease characterized by progressive muscle weakness from anterior horn degeneration. Nusinersen has recently been approved as a disease-modifying drug for SMA that needs to be administered intrathecally. Its injection is often associated with extreme difficulty since patients with SMA have severe vertebral deformity and may be with vertebral instrumentation. Case description: A 21-year-old female with type 2 SMA and spinal defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Nevertheless, cervical approaches are used off label, and little is known about their influence in the pharmacodynamics or efficacy of nusinersen. To the best of our knowledge, the US‐guided lumbar puncture has scarcely been reported to treat SMA patients with complex spines [13]. In this study, all patients younger than 20 years old could be treated and our success rate (96.8%) was similar to previously reported transforaminal approaches [6–9].…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, cervical approaches are used off label, and little is known about their influence in the pharmacodynamics or efficacy of nusinersen. To the best of our knowledge, the US‐guided lumbar puncture has scarcely been reported to treat SMA patients with complex spines [13]. In this study, all patients younger than 20 years old could be treated and our success rate (96.8%) was similar to previously reported transforaminal approaches [6–9].…”
Section: Discussionsupporting
confidence: 82%
“…Transforaminal approach is effective but presents a higher risk of radicular artery puncture than the interlaminar approach. [20][21][22][23] US or fluoroscopy guided cervical punctures are also described [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] but are used off label and their impacts on nusinersen efficacy are unknown. A recent US guided interlaminar lumbar approach has been proposed and presented as safe and effective: in that paper, 18 SMA patients (children, adolescents, adults) with severe scoliosis and spondylodesis were treated, with a high percentage of success (96.8% of attempts, 77.8% of all patients, 50% of adult patients) and very few AEs.…”
Section: Discussionmentioning
confidence: 99%
“…We report our experience in US assisted intrathecal nusinersen administration in SMA adults with difficult spines and previous difficulties in successfully undergoing intrathecal treatments, in order to expand the limited evidence so far reported 5‐17 and to encourage the use of US to facilitate intrathecal access.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ultrasound (US) is recognized as a useful adjunct for lumbar spinal anesthesia in adults, there are only a few papers on US utilization for intrathecal nusinersen delivery in spinal muscle atrophy (SMA) patients, all of which describe intrathecal nusinersen delivery via the translaminar approach 1‐6 . Veiga‐Canuto et al reported that US‐guided translaminar approach was unsuccessful in patients without visible interlaminar space on pre‐procedural computed tomography (CT) 2 .…”
Section: Introductionmentioning
confidence: 99%